Urban heat islands in small and medium-sized cities in Brazil and the context of climate change - Costa Trindade Amorim, Margarete Cristiane de [UNESP] (Revues Org, 2020)
Since the constitution of the planet, the climate has been both warmer and colder, and both drier and more humid than current conditions. Nevertheless, we are facing strong changes in the natural landscape resulting from human actions, particularly in urban areas, which are capable of generating a specific urban climate. The urban territorial expansion and the activities performed by society interfere in the energy balance as a result of the replacement of vegetation by buildings and soil waterproofing, as well as by the generation of anthropogenic heat, associated with human activities. The consequences of such changes are the urban heat islands, which are characterized by an increase in temperature in cities in relation to the adjacent rural areas. This paper aims to analyze climate change on a local scale, particularly in the generation of heat islands in cities of medium and small size located in the continental tropical environment, and, as an analytical example, episodes of the dry season. Considerations were also presented about the scalar complexity in which climate change is involved. For this reason, the importance of small and medium-sized cities in Brazil was reflected, due to the economic and social expression they have taken in recent years. Hourly air temperature data were recorded by automatic weather stations in urban and rural areas in the cities of Presidente Prudente (SP), Rosana (SP), Paranavai (PR) and Nova Andradina (MS). The analysis of the hourly variability of heat islands demonstrated that, when there is a lack of effective planning and management actions, small and medium-sized cities present heat islands of very strong magnitude (above 6 degrees C), which highlights the severity of the diagnosed results and points to the need for measures to mitigate climate change at the local scale.
Keywords: Heat islands intensities; local scale; Brazil